Plumage iridescence is associated with distinct feather microbiota in a tropical passerine - Javůrková, Veronika Gvoždíková; Enbody, Erik D; Kreisinger, Jakub; Chmel, Kryštof; Mrázek, Jakub; Karubian, Jordan (Scientific reports, 2019)
Birds present a stunning diversity of plumage colors that have long fascinated evolutionary ecologists. Although plumage coloration is often linked to sexual selection, it may impact a number of physiological processes, including microbial resistance. At present, the degree to which differences between pigment-based vs. structural plumage coloration may affect the feather microbiota remains unanswered. Using quantitative PCR and DGGE profiling, we investigated feather microbial load, diversity and community structure among two allopatric subspecies of White-shouldered Fairywren, Malurus alboscapulatus that vary in expression of melanin-based vs. structural plumage coloration. We found that microbial load tended to be lower and feather microbial diversity was significantly higher in the plumage of black iridescent males, compared to black matte females and brown individuals. Moreover, black iridescent males had distinct feather microbial communities compared to black matte females and brown individuals. We suggest that distinctive nanostructure properties of iridescent male feathers or different investment in preening influence feather microbiota community composition and load. This study is the first to point to structural plumage coloration as a factor that may significantly regulate feather microbiota. Future work might explore fitness consequences and the role of microorganisms in the evolution of avian sexual dichromatism, with particular reference to iridescence.
Keywords: Biodiversity; taxonomické DNA čárové kódování; Male; mikrobiota; biodiverzita; mužské pohlaví; Feathers; Microbiota; DNA Barcoding, Taxonomic; Nová Guinea; Pigmentation; Animals; ženské pohlaví; zvířata; peří; Passeriformes; New Guinea; Female; pigmentace